Плазменные низкоэмиссионные покрытия для теплосберегающих зданий и сооружений - Асаинов О. Х. Олег Хайдарович; Баинов Д. Д. Даши Дамбаевич; Кривобоков В. П. Валерий Павлович; Пащенко О. В. Олег Валентинович (2007, 2007)
В фонде НТБ ТПУ отсутствует